2018
DOI: 10.1186/s40623-017-0776-2
|View full text |Cite
|
Sign up to set email alerts
|

Strain localization and fabric development in polycrystalline anorthite + melt by water diffusion in an axial deformation experiment

Abstract: We performed two axial deformation experiments on synthetic polycrystalline anorthite samples with a grain size of ~ 3 μm and 5 vol% Si-Al-rich glass at 900 °C, a confining pressure of 1.0 GPa, and a strain rate of 10 −4.8 s −1. One sample was deformed as-is (dry); in the other sample, two half-cut samples (two cores) with 0.15 wt% water at the boundary were put together in the apparatus. The mechanical data for both samples were essentially identical with a yield strength of ~ 700 MPa and strain weakening of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Consequently, its progress is crucial for our understanding of crustal dynamics. Fukuda et al (2018) showed how the addition of small amounts of water to polycrystalline anorthite under high temperature induces a change from distributed fracturing to plastic flow promoting grain-size-sensitive creep in the lower middle crust. Kameda et al (2017) investigated the alteration and dehydration of subducting oceanic crust, specifically pillow basalts within the Shimanto belt showing how the saponite-chlorite conversion within mixed layer C/S minerals may contribute fluid to plate boundary fault systems with consequent mechanical effects.…”
mentioning
confidence: 99%
“…Consequently, its progress is crucial for our understanding of crustal dynamics. Fukuda et al (2018) showed how the addition of small amounts of water to polycrystalline anorthite under high temperature induces a change from distributed fracturing to plastic flow promoting grain-size-sensitive creep in the lower middle crust. Kameda et al (2017) investigated the alteration and dehydration of subducting oceanic crust, specifically pillow basalts within the Shimanto belt showing how the saponite-chlorite conversion within mixed layer C/S minerals may contribute fluid to plate boundary fault systems with consequent mechanical effects.…”
mentioning
confidence: 99%
“…Therefore, the deformation behaviour of these rocks, but also the chemical reactions taking place in them, will depend on the physical and chemical properties of plagioclase. Besides studies investigating the mechanical behaviour of plagioclase‐rich rocks over a broad pressure ( P ) temperature ( T )–strain rate ( trueε̇) range (Fukuda et al, 2018; Fukuda et al, 2022; Rybacki et al, 2006; Rybacki & Dresen, 2004; Tullis, 2018; Tullis & Yund, 1992, 1987), there are also studies focusing on the impact of plagioclase breakdown at high pressure (H P ) conditions. This decomposition of plagioclase at H P is considered as one of the most important metamorphic reactions in the crust, and the modalities of its breakdown directly control the mechanical behaviour of the reacting rock (Stünitz & Tullis, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The water content is known as one of the most notable factors for lowering the strength of rocks [31]. A large number of studies [32][33][34] consistently show that the water-rock interaction undermines the mechanical property of rock, which is mainly found expressed in strength decrease, the change of the deformation, and failure characteristics. Li et al [35] suggested that moisture content has a significant effect on shear properties reduction of both sandstone and mudstone, which must be considered in mining or excavation processes.…”
Section: Introductionmentioning
confidence: 99%